Semiparametric Accelerated Failure Time Model as a New Approach for Health Science Studies - Mostafa KARIMI; Ardalan SHARIAT (Iranian Journal of Public Health, 2017)
Semiparametric Accelerated Failure Time Model as a New  Approach for Health Science Studies